Two young lumbermen - Stratemeyer, Edward, 1862-1930; Shute, A. B. (Augustus Burnham), 1851-1906 (Salt Lake City, UT : Project Gutenberg, 2023)
"Two Young Lumbermen: or, From Maine to Oregon for Fortune" by Edward Stratemeyer is a novel written in the early 20th century. This engaging tale follows two young lumbermen, Dale Bradford and Owen Webb, as they navigate the challenges of the lumber trade in Maine and Oregon during a time of economic transition and opportunity. The story aims to depict not only their adventures in the woods but also the importance of the lumber industry in America, immersing readers in the hardships and triumphs associated with this crucial trade. The opening of the novel presents Dale Bradford, an orphaned young man recently engaged in work at a lumber mill owned by John Larson. As the mill faces a shutdown due to a lack of logs, Dale's concern for his financial situation becomes apparent. He reflects on the legacy of his late father, who had invested in land in Oregon that had not yielded fortune and left Dale in debt. As Dale finds companionship with Owen Webb, the two set their sights on employment opportunities further afield, determined to better their circumstances. Events unfold that introduce them to the challenges and dangers of the lumber industry, setting the stage for their journey and personal growth as they head into the deep woods and face encounters that test their resolve. (This is an automatically generated summary.)
Release date is 2023-08-17
David Edwards, Mary Meehan and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Maine -- Juvenile fiction; Lumbermen -- Juvenile fiction; Logging -- Juvenile fiction; Oregon -- Juvenile fiction